CHANGES IN TOTAL PHENOL CONTENT AND ANTIOXIDANT ACTIVITY OF GREEK TABLE OLIVE CULTIVAR AMFISSIS DURING MATURATION - GOUGOULIAS, Nikolaos; GIURGIULESCU, Liviu; VAGELAS, Ioannis; WOGIATZI, Eleni; NTALLA, Maria-Nektaria (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The Amfissis cultivar olive fruits grown in the region of Larissa, central Greece, were studied for the changes in total polyphenol content, phenolic fractions and antioxidant capacity during maturation period (four months). It has been established that the total phenol content and antioxidant capacity, change in broad ranges depending on the ripening stage of fruits. The content of total phenols in the Amfissis cultivar during maturation varied from 3.9 to 11.9 mg (GAE) g-1 FW. The highest content of total phenols has been found in the harvest stage (December). The content of flavonoid phenols ranges from 3.12 to 9.47 mg (GAE) g-1 FW. The highest content of flavonoid phenols was determined the time period of the harvesting. The content of non-flavonoid phenols during ripening of olive fruit ranges from 0.78 to 2.43 mg (GAE) g-1 FW. The highest content of NFP was determined the time period of the harvesting (black color). The inhibition concentration (IC50) of extract during maturation of the olive fruit in all stages ranges from (735 to 130) mg/l. The lowest inhibition concentration (highest antioxidant capacity) was observed in the collection stage of the olive fruits. The obtained results have a direct impact on the harvesting date of the table cultivar Amfissis, influencing the sensory properties and the quality of the olive fruit.